Electrostatically supported surface coating of solid particles using liquid nitrogen - Wirth, Karl-Ernst; Bindl, Hubert Christian (Proceedings PARTEC 2001, 2001)
The homogenous coating of particles in the micrometer range with fine-grained particles in the nanometer range leads to increasing flowability of the powder. Experiments have been carried out concerning the selective charging and coating of solid particles in liquid nitrogen. Liquid nitrogen as a suspension medium for solid particles offers certain advantages in comparison to other liquids and especially to gases. The charging of the fine-grained particles was realized by triboelectric charging as well as contact charging at metal electrodes at which a certain high voltage is applied. With selective charging of fine-grained solid particles, the coating quality of a powder mixture can be improved significantly. With respect to the use of coated particles in Dry-Powder-Inhalers (DPIs), the share of respirable particles reaching the lung is very high.
UnivIS-Import:2015-04-16:Pub.2001.tech.ITC.mechve.electr
Keywords: Mixing; Coating; Electrostatic charge; Liquid nitrogen; Dry-Powder-Inhaler